Beyond the clinic: a community-embedded, multidomain framework for early detection of glaucoma - Akiko Hanyuda; Tetsuya Yamada; Satoru Tsuda; Noriko Himori; Toru Nakazawa (Frontiers in Public Health, 2026)
Glaucoma remains one of the leading causes of acquired irreversible blindness worldwide, with normal-tension glaucoma representing the dominant subtype in Japan and several East Asian populations. The insidious, asymptomatic progression of this condition, combined with the demonstrated inadequacy of intraocular pressure alone as a screening criterion, creates a critical gap between disease burden and case detection. Population-based epidemiological studies consistently reveal that the majority of individuals with glaucoma are undiagnosed. Two responses have been suggested: incorporation of retinal imaging into annual health checkups, which warrants formal prospective evaluation, and characterization of individuals at higher risk — integrating genomic risk, oxidative stress biomarkers, systemic lifestyle factors, and ocular blood flow dynamics — which may help identify those in whom damage is most likely to occur. The principal contribution of this Perspective is therefore the implementation model rather than the individual screening components. We introduce the Living Lab (‘neighborhood health lab’), a community co-creation platform established under the Japan Science and Technology Agency COI-NEXT ‘Vision to Connect’ hub at Tohoku University, as a scalable model for operationalizing this framework. Embedded within commercial retail environments, the Living Lab integrates non-invasive screening, longitudinal health data collection, and evidence-based health product development—exemplified by the Ronbun Recipe ® concept—within a stakeholder-aligned ecosystem encompassing citizens, researchers, industry, and municipal authorities. Conceived as a platform for well-being rather than as a disease-specific screening service, it engages individuals who are asymptomatic, undiagnosed, and outside existing screening pathways, and who would not otherwise be assessed at all.